Refining the Supported Decision Making Inventory. Issue 3 (14th February 2020) - Shogren, Karrie A.; Rifenbark, Graham G.; Wehmeyer, Michael L.; Dean, Evan E.; Killeen, Mary B.; Karsevar, Judith
Abstract: This paper reports the steps taken to refine the pilot version of the supported decision making inventory (SDMI), a new tool designed to support planning teams implementing supported decision making with people with disabilities. Data were collected on the pilot version of the SDMI with 152 adults with intellectual and developmental disabilities and their supporters and systematic analyses were undertaken to identify the best subset of items on the pilot version of the SDMI. Analyses were also undertaken to examine the impact of contextual factors on scores on the refined tool. The reduced set of items ( n = 29) adequately represented the three theoretical domains assessed on the scale: (1) personal factors, (2) environmental demands, and (3) the supports needed to engage in decision‐making. With the reduced set of items, age, gender, and having multiple disability labels did not influence scores. Those that had a legal guardian scored lower in experiences with decision making but higher in supports needed for implementing a decision. Additionally, those that were in competitive, integrated employment identified having more experiences with decision‐making and scored lower on supports needed for making a decision. Implications for research, policy, and practice are described.